IKTIOFAUNA RAWA BANJIRAN SUNGAI KAMPAR KIRI [Ichthyofauna in Floodplain of Kampar Kiri River] - Charles PH. Simanjuntak; M F. Rahardjo; Sutrisno Sukimin (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2006)
The aim of study is to describe the richness of ichthyofauna of floodplain of Kampar Kiri River. Icthyofauna study was conducted from June to December 2006. Method that used was purposive sampling where many gears were used. A total of 86 species belonging to 21 families and 44 genera was found. Cyprinidae was dominant, comprising 35 species or 40.7%, followed by Silluridae comprising 11 species or 12.8%. The high number of species richness was recorded for the floodplain of Kampar Kiri River.